Ferroelectret nanogenerators for loudspeaker applications: A comprehensive study. (3rd March 2020) - Dsouza, Henry; Van Schyndel, Andre; Pastrana, Juan; Cao, Yunqi; Hunter, Eric; Rakerd, Brad; Sepúlveda, Nelson
Abstract: A ferroelectret nanogenerator (FENG) was recently developed as a flexible energy harvesting device with bi-directional capability between electrical and mechanical energy domains, and its use as a loudspeaker/microphone was demonstrated. Dependencies of Sound Pressure Levels (SPLs) generated by FENG due to an AC voltage stimulus, surface area, geometric shape, and addition of layers are presented here. Also, the relation between the sound output to the electrical input is studied and shown to be linear, which demonstrates that these flexible loudspeakers have low distortion within the human audible range of 20 Hz to 20 kHz. A study for ultrasonic frequencies up to 40 kHz is also presented. A theoretical model relating the electrical and acoustical domain of the FENG is developed based on the experimental observations made and using Boundary Element Methods (BEM) to accurately mimic the testing environment for simulation purposes. The comparison between this model and the actual behavior is presented under several cases and observed to be closely correlated.